2002
DOI: 10.1111/j.1749-6632.2002.tb04607.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Chemokine Receptor CXCR4 and Its Ligand Stromal Cell‐Derived Factor 1 in Human Brain Tumors and Their Involvement in Glial Proliferation in Vitro

Abstract: Chemokines are a family of proteins that chemoattract and activate cells by interacting with specific receptors on the surface of their targets. They are grouped into four classes based on the position of key cysteine residues: C, CC, CXC, and CX3C. Stromal cell-derived factor 1 (SDF1), the ligand of the CXCR4 receptor, is a CXC chemokine involved in chemotaxis and brain development that also acts as coreceptor for HIV-1 infection. It has been proposed that CXCR4 is overexpressed and required for proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 25 publications
0
79
1
2
Order By: Relevance
“…Previous cell culture studies have provided evidence that signals from glial cells influence development of the GABAergic phenotype of hippocampal neurons during early postnatal development (52). Although the identity of the glial cell-derived factor is unknown, SDF1␣ is one possibility as it is known to be produced by astrocytes (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cell culture studies have provided evidence that signals from glial cells influence development of the GABAergic phenotype of hippocampal neurons during early postnatal development (52). Although the identity of the glial cell-derived factor is unknown, SDF1␣ is one possibility as it is known to be produced by astrocytes (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…However, CXCR-4 has been found to be upregulated on malignant glioma. 9,[23][24][25][26] In a seminal article, Zhou et el., showed that CXCR4 on glioma lines is a signaling receptor in that its agonist, stromal cell-derived factor-1 (SDF-1; CXCL12), produced rapid phosphorylation of mitogen-activated protein kinases. 9 Furthermore, SDF-1 induced the phosphorylation of Akt (protein kinase B), a kinase associated with survival, and prevented the apoptosis of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some cytokines, such as stromal cell-derived factor 1 (SDF-1) (Barbero et al, 2003), epidermal growth factor (EGF) (Held-Feindt et al, 2003) and IL-6 (Goswami et al, 1998), have been reported to be produced and to increase cell proliferation in glioblastoma cell lines. We investigated whether the addition of APRIL affected the secretion of one of these molecules, IL-6.…”
Section: Discussionmentioning
confidence: 99%